2013
DOI: 10.2478/romneu-2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with recurrence of postoperative meningioma: a clinical study of 138 patients

Abstract: Background and purpose: As the postoperative recurrence of meningioma can have devastating effects, it is important to identify factors that can be used to predict this type of tumor recurrence. Material and methods: We have performed a retrospective study involving 138 patients who were surgically treated for intracranial meningioma between 2005 and 2010. The patient population consisted of 80 females and 58 males, with an age range of 23 to 77 years old (mean age = 52 years). We measured associations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Numerous studies showed association between Ki67 LI and PTBE, as well as between Ki67 LI and invasive behavior of meningiomas. Meningiomas with higher Ki67 LI lead to a higher frequency of PTBE ( 6 , 14 ). Our study showed significant correlation between Ki67 LI and EI, consistent with the literature ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies showed association between Ki67 LI and PTBE, as well as between Ki67 LI and invasive behavior of meningiomas. Meningiomas with higher Ki67 LI lead to a higher frequency of PTBE ( 6 , 14 ). Our study showed significant correlation between Ki67 LI and EI, consistent with the literature ( 6 ).…”
Section: Discussionmentioning
confidence: 99%